Reckoning with Anti-Asian Violence: Racial Grief, Visionary Organizing, and Educational Responsibility. Issue 4 (4th July 2021) - Coloma, Roland Sintos; Hsieh, Betina; Poon, OiYan; Chang, Stephanie; Choimorrow, Sung Yeon; Kulkarni, Manjusha P.; Meng, Grace; Patel, Leigh; Tintiangco-Cubales, Allyson
Abstract: This commentary is an edited transcription of a historic and dynamic discussion on "Reckoning with Anti-Asian Violence" among a distinguished panel of elected legislators, community leaders, and academic researchers. This discussion took place virtually as a presidential session during the annual meeting of the American Educational Research Association on April 11, 2021, in response to the increasing attention as well as escalating fear due to anti-Asian racism and violence in the United States and globally, including the mass shooting in Atlanta on March 16, 2021. Over 100 attendees across the United States and internationally bore witness to this important yet rare convening of high-profile Asian American female politicians, organizers, and scholars. Many recognized the historic significance of this topic and gathering and asked for its documentation. As session organizers and panelists, we offer this commentary for our communities as part of a national and global archive of the current state of affairs.